2015
DOI: 10.1590/0004-282x20150161
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic basis of familial amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis represents the most common neurodegenerative disease leading to upper and lower motor neuron compromise. Although the vast majority of cases are sporadic, substantial gain has been observed in the knowledge of the genetic forms of the disease, especially of familial forms. There is a direct correlation between the profile of the mutated genes in sporadic and familial forms, highlighting the main role ofC9orf72 gene in the clinical forms associated with frontotemporal dementia spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…Chen et al [103]- [105] identified PON2, Eykens et. al [106] identified APOE and Souza et al [107], [108] identified ITPR2 and VAPB genes associated with ALS which consistent with our study. Fahey et al [109] identified the TENM1 gene associated with CP and consistent with our study.…”
Section: E Potential Targets Verification Using Gold Benchmark Databsupporting
confidence: 91%
See 2 more Smart Citations
“…Chen et al [103]- [105] identified PON2, Eykens et. al [106] identified APOE and Souza et al [107], [108] identified ITPR2 and VAPB genes associated with ALS which consistent with our study. Fahey et al [109] identified the TENM1 gene associated with CP and consistent with our study.…”
Section: E Potential Targets Verification Using Gold Benchmark Databsupporting
confidence: 91%
“…Inositol 1, 4, 5-trisphosphate receptor type 2 (ITPR2) is involved in many processes including cell migration, cell division, smooth muscle contraction, and neuronal signaling. A mutation in this gene has been associated with ALS and HD [107]. Vesicle-associated membrane protein-associated protein B (VAPB) is an integral endoplasmic reticulum membrane protein, which has various functions such as intracellular vesicle trafficking, lipid transport, and the unfolded protein response and associated with ALS [107].…”
Section: E Potential Targets Verification Using Gold Benchmark Databmentioning
confidence: 99%
See 1 more Smart Citation
“…There are six familial ALS types allegedly linked with JALS, which correspond to mutations in the following genes: ALS2 (ALS type 2), SETX (ALS type 4), SPG11 (ALS type 5), FUS (ALS type 6), UBQLN2 (ALS type 15) and SIGMAR1 (ALS type 16). 25 , 26 …”
Section: Cognitive Dysfunction In Other Motor-neuron Disordersmentioning
confidence: 99%
“…Two different forms of the disease are known: familial ALS (5-10 %) and sporadic ALS (90-95 %); both forms share initial symptoms, muscle weakness and cramping. Even though ALS pathophysiology still has to be clearly understood, numerous mechanisms are involved in its development, including oxidative stress, inflammation, protein misfolding, protein aggregation, altered RNA splicing and signaling, defects in axonal transport, mitochondrial dysfunctions, glutamate excitotoxicity, loss of proteostasis, and primary and secondary ion channel defects [33,34]. Although enormous efforts have been made to develop agents that could be used to counteract neurodegenerative disorders, no drugs and therapies are available to definitively halt the progression of these debilitating diseases.…”
Section: Introductionmentioning
confidence: 99%